Comparison of Mortality among Severe Trauma Patients Treated in a Trauma Centre versus a Non-Trauma Centre. Issue 1 (January 2017) - Lai, CH; Lai, CH; Chen, KH; Wang, CH; Hsiao, CT; Hsiao, KY
Introduction: In Taiwan, patients with major trauma are often sent to the closest non-trauma centre for initial resuscitation and transferred to distant trauma centres subsequently. This study aimed to evaluate the in-hospital mortality of severe trauma patients treated in a trauma centre versus in a non-trauma centre. Methods: This prospective observational study reviewed 223 patients with major trauma (defined as Injury Severity Scale [ISS] score >15) who visited either a Level I trauma centre or a non-trauma centre from April 2013 to March 2014. Data of clinical status, trauma mechanisms, laboratory and radiology, interventions, and mortality/survival were evaluated. Logistic regression analysis was performed to assess effects of initial hospital treatment on mortality. Results: A total of 158 major trauma patients were taken to the trauma centre hospital, and 65 patients were taken to the non-trauma centre. Age > 70 years (odds ratio [OR] 6.24, 95% confidence interval [CI] 1.01 to 38.62, compared to age ≤40 years), Glasgow Coma Scale [GCS] 3-8 (OR 19.00, 95% CI 2.30-157.01, compared to GCS 13-15), GCS 9-12 (OR 28.88, 95% CI 4.40-189.86, compared to GCS 13-15), ISS score >25 (OR 6.95, 95% CI 1.27-38.08) and taken to non-trauma centre initially (OR 30.90, 95% CI 5.00-191.27) were significantly associated with mortality. Conclusion: Initial treatment of patients with major trauma in a non-trauma centre was associated with increased mortality compared to initial treatment in a trauma centre.